Studi Evaluasi Kinerja Anggota Tim Sahabat Pelanggan Di RSUD Kota Bogor - Patrick Patrick; Sri Sundari; Marisi Pakpahan (Master Manajemen, 2024)
This This study evaluates the performance of the customer friend team at the Regional General Hospital (RSUD) of Bogor City and analyzes the factors influencing their performance. The study adopts a qualitative field research method. Effective performance evaluation has been found to enhance employee competence and motivation, while ineffective evaluation can have negative repercussions such as employee complaints, decreased motivation, and turnover. Critical factors influencing the customer friend team's performance include inter-team coordination, customer engagement, and interpersonal communication skills. Training and skill fulfillment are also vital in improving employee performance. Effective performance evaluation aids RSUD Bogor City in enhancing employee competence, work motivation, and achieving organizational goals optimally. Factors such as fairness, transparency, and clear and constructive feedback are important considerations in performance evaluation. The study findings provide a better understanding of the factors influencing the customer friend team's performance and offer practical implications for RSUD Bogor City to enhance service quality and patient relations.